2015
DOI: 10.1523/jneurosci.3381-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

MuSK Frizzled-Like Domain Is Critical for Mammalian Neuromuscular Junction Formation and Maintenance

Abstract: The muscle-specific kinase MuSK is one of the key molecules orchestrating neuromuscular junction (NMJ) formation. MuSK interacts with the Wnt morphogens, through its Frizzled-like domain (cysteine-rich domain [CRD]). Dysfunction of MuSK CRD in patients hasbeen recently associated with the onset of myasthenia, common neuromuscular disorders mainly characterized by fatigable muscle weakness. However, the physiological role of Wnt-MuSK interaction in NMJ formation and function remains to be elucidated. Here, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 56 publications
(37 reference statements)
1
76
1
Order By: Relevance
“…Inhibition of glycogen synthase kinase 3␤ activates ␤-catenin signaling. LiCl has been used recently to determine Wnt canonical pathway in NMJ formation (Messéant et al, 2015). We used this method to determine whether ␤-catenin activation mitigates NMJ formation deficits in HSA-Yap Ϫ/Ϫ mice.…”
Section: Partial Rescue Of Nmj Formation and Regeneration Deficits Bymentioning
confidence: 99%
“…Inhibition of glycogen synthase kinase 3␤ activates ␤-catenin signaling. LiCl has been used recently to determine Wnt canonical pathway in NMJ formation (Messéant et al, 2015). We used this method to determine whether ␤-catenin activation mitigates NMJ formation deficits in HSA-Yap Ϫ/Ϫ mice.…”
Section: Partial Rescue Of Nmj Formation and Regeneration Deficits Bymentioning
confidence: 99%
“…A recent study reported that prepatterned AChRs were almost undetectable and that synapse formation and motor performance were severely impaired in mice that are mutant for the MuSK Fz-like domain (Messéant et al 2015). However, Messéant et al (2015) did not examine the patterning of AChR expression prior to or independent of innervation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that prepatterned AChRs were almost undetectable and that synapse formation and motor performance were severely impaired in mice that are mutant for the MuSK Fz-like domain (Messéant et al 2015). However, Messéant et al (2015) did not examine the patterning of AChR expression prior to or independent of innervation. Even at the earliest stage examined by Messéant et al (2015), motor axons had innervated the diaphragm muscle, precluding investigation of the role of the MuSK Fz-like domain in muscle prepatterning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations